Tantangan Pengelolaan Perguruan Tinggi Pesantren yang Bermutu dalam Revolusi Industri Keempat - Taufiqur Rahman Taufiqur Rahman; Junaidi Junaidi (Jurnal Pendidikan Islam Indonesia, 2019)
Higher education in Pesantren gain its competitive advantage through reputation of Pesantren. A development of the Higher Education is built on tradition of Pesantren which often contradict with modern trend. The goal to develop a quality higher education in Pesantren requires the institution to adjust with external environment about its concept and infrastructure. The adjustment is acted hierarcically from its quality policy to work instruction of day-to-day management.